2013
DOI: 10.1044/1092-4388(2013/12-0210)
|View full text |Cite
|
Sign up to set email alerts
|

An EMG Study of the Lip Muscles During Covert Auditory Verbal Hallucinations in Schizophrenia

Abstract: Purpose: Auditory verbal hallucinations (AVHs) are speech perceptions in the absence of a external stimulation. An influential theoretical account of AVHs in schizophrenia claims that a deficit in inner speech monitoring would cause the verbal thoughts of the patient to be perceived as external voices. The account is based on a predictive control model, in which verbal self-monitoring is implemented. The aim of this study was to examine lip muscle activity during AVHs in schizophrenia patients, in order to che… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 65 publications
(75 reference statements)
1
24
0
1
Order By: Relevance
“…Instead, it has been used to study, for instance, silent recitation (Livesay et al, 1996), speech in stutterers (Choo et al, 2010), covert verbal hallucinations in schizophrenia (Rapin et al, 2013), and articulation by aging participants (Rastatter et al, 1987b) and by articulatory disordered children (Rastatter et al, 1987a). The muscle complex that has typically been focused on is the orbicularis oris (OO), which is situated in the lips and controls lip posture during overt speech.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, it has been used to study, for instance, silent recitation (Livesay et al, 1996), speech in stutterers (Choo et al, 2010), covert verbal hallucinations in schizophrenia (Rapin et al, 2013), and articulation by aging participants (Rastatter et al, 1987b) and by articulatory disordered children (Rastatter et al, 1987a). The muscle complex that has typically been focused on is the orbicularis oris (OO), which is situated in the lips and controls lip posture during overt speech.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown subtle muscle activity in speech musculature using sEMG during verbal mental imagery, silent reading, and silent recitation (Jacobson, 1931;Livesay, Liebke, Samaras, & Stanley, 1996;McGuigan & Dollins, 1989). Also, activity in the OOI and the STH muscles was significantly higher when patients with schizophrenia reported hallucinations (Rapin, Dohen, Polosan, Perrier, and Loevenbruck, 2013). Lip muscles activation, as recorded in sEMG, was higher during covert speech, compared to activation in a silent visualization task (Livesay et al, 1996).…”
Section: Introductionmentioning
confidence: 86%
“…We think that we can explain the sense of agency experienced when thinking if we move in that direction. Even though the application of the model to the cognitive domain may not be straightforward (see, e.g., Frith, 2012;Vicente, 2014), it is plausible that models such as those proposed by Rapin et al (2013), Swiney and Sousa (2014) and L{venbruck et al (forth. ), which explain agency in inner speech in terms of comparisons between goal states and predicted states, could also explain agency in UT.…”
Section: The Linguistic Nature Of Unsymbolized Thinkingmentioning
confidence: 99%